A systematic review on the prognostic role of radiologically-proven sarcopenia on the clinical outcomes of patients with acute pancreatitis. - Khang Duy Ricky Le; Harsh Patel; Emma Downie (PLoS ONE)
Background Sarcopenia is a known risk factor for poor prognosis in chronic pancreatitis, however the impact of sarcopenia in acute pancreatitis (AP) is unknown. This systematic review examines the prognostic impact of sarcopenia on clinical outcomes in patients with acute pancreatitis. Methods A systematic literature of Medline, EMBASE, Cochrane, and the World Health Organisation International Clinical Trials Registry Platform was undertaken to identify articles relating to sarcopenia, AP, and computed tomography imaging. Data collected was related to studies' demographic population, presence of sarcopenia, sarcopenia assessment methodology, obesity, pancreatitis severity, and short- and long-term complications of AP. Results A total of four out of 114 unique peer-review articles were included in this review, encompassing 947 patients in total. Of the analysable data, 200 patients had sarcopenia and 640 did not. There was marked heterogeneity in the determination of the presence of sarcopenia between studies. No significant association was found between sarcopenia and pancreatic necrosis, organ failure, venous thromboembolism, recurrent acute pancreatitis, or mortality. Conclusion Sarcopenia remains highly prevalent in patients suffering from acute pancreatitis. There is insufficient evidence to suggest sarcopenia is associated with poorer outcomes in patients with acute pancreatitis. More high-powered studies are required to further characterise the impact of sarcopenia on patients with acute pancreatitis.